Building up Graphene-Based Conductive Polymer Composite Thin Films Using Reduced Graphene Oxide Prepared by γ-Ray Irradiation - Siyuan Xie; Bowu Zhang; Chunlei Wang; Ziqiang Wang; Linfan Li; Jingye Li (The Scientific World Journal)
In this paper, reduced graphene oxide (RGO) was prepared by means of γ-ray irradiation of graphene oxide (GO) in a water/ethanol mix solution, and we investigated the influence of reaction parameters, including ethanol concentration, absorbed dose, and dose rate during the irradiation. Due to the good dispersibility of the RGO in the mix solution, we built up flexible and conductive composite films based on the RGO and polymeric matrix through facile vacuum filtration and polymer coating. The electrical and optical properties of the obtained composite films were tested, showing good electrical conductivity with visible transmittance but strong ultraviolet absorbance.